Circumstances and paths of change and stability in knowledge network - Basile, C. (Cranfield University, 2012)
To cast light on the impact of knowledge on economic growth, performance and innovation is a highly sought-after research endeavour that keeps triggering interest across different disciplines. This in turn calls for the need to explain how processes of knowledge creation, transfer and use occur. A fast-growing body of research argues that the characteristics of social relationships and the network they constitute may provide a better understanding of knowledge processes. However, the great majority of empirical works in the field has concentrated on static analysis, addressing the effect that structural and relational properties of social networks exert over knowledge outcomes In this work I aim to extend the current understanding on knowledge network research by conducting a systematic review of longitudinal knowledge network research. I believe that it is by looking at longitudinal empirical investigation that we can get a grasp of dynamic processes such as those related to knowledge. I propose therefore a framework to organize knowledge network research, highlighting points of conflicts and coherence across different levels of analysis, network elements and constructs adopted. Emerging themes and future areas of research are explored.